Exploring the Validity of a Creative Personality Scale in University Settings: A Confirmatory Factor Analysis Approach - Rahmat Aziz; Fathul Lubabin Nuqul; Endah Kurniawati Purwaningtyas; Yulia Sholichatun; Forbis Ahamed (Jurnal Pendidikan Progresif, 2024)
Exploring the Validity of a Creative Personality Scale in University Settings: A Confirmatory Factor Analysis Approach. Objective: This study aims to validate a revised 24-item Creative Personality Scale explicitly tailored for university students using Confirmatory Factor Analysis (CFA). The scale addresses gaps in existing tools initially designed for high school students and offers a more accurate fit for higher education contexts. Methods: A sample of 804 students from various faculties was selected through stratified random sampling to ensure diverse representation. The scale was revised after the initial analysis revealed inconsistencies in certain items within the university context. CFA was then employed to assess the revised scale's construct validity and reliability. Findings: The revised scale demonstrated significant improvements in internal consistency, with Cronbach's Alpha increasing from 0.823 to 0.858. Additionally, model fit indices were favourable, with a Comparative Fit Index (CFI) of 0.92 and a Root Mean Square Error of Approximation (RMSEA) of 0.04, indicating strong model validity. Conclusion: This validated scale provides a reliable and accurate tool for assessing creativity in university students. It enables educational institutions to support better creativity development, which is increasingly essential for academic and professional success. The findings significantly contribute to educational psychology by providing a context-sensitive instrument for higher education. Keywords: confirmatory factor analysis, creative personality scale, internal consistency, validity, and reliability.DOI: http://dx.doi.org/10.23960/jpp.v14.i2.202494